Femtosecond laser-induced nonlinear absorption in thick polystyrene - Wang, Bing (2021)
The nonlinear absorption behavior of thick polystyrene sample was experimentally investigated and theoretically analyzed. As polystyrene is transparent to the applied laser wavelength, the absorption was mainly through nonlinear absorption by the bulk material. The effective second order nonlinear absorption coefficient (β) was determined with the z scan technique. The nonlinear behavior at different laser powers: 5.2 mW, 10.4 mW, 14.4 mW and 23.5 mW were investigated. The transmittance of laser energy was measured and a significant change was observed with different sample distance from the laser focal plane. By treating the thick polystyrene sample as a stack of thin layers, the effective nonlinear absorption coefficient was determined to be 0.000695 m/W with a standard deviation of 0.000026.